Comparative Measurement/Analysis of Field Agronomic Yield, Quality and Measurements of the Crop in the Traditional and Improved Management Systems - International Livestock Research Institute (International Livestock Research Institute, 2015)
Trade-off analysis of BROAD BEANS/forage production system. To learn more about this dataset, please visit the ILRI Datasets Portal http://data.ilri.org/portal/dataset/faba_analysis